Enhancing the performance of fibre-based packaging for climacteric fruits with biobased films infused with bioactive compounds and biosensors - Baard, Vejonepher Dominique (Stellenbosch : Stellenbosch University, 2025)
Baard, V. D. 2025. Enhancing the performance of fibre-based packaging for climacteric fruits with biobased films infused with bioactive compounds and biosensors. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/695f3c40-22b6-43c1-a9a2-9d0fdcb1a8e1